Preparing quality teachers: Bridging the gap between tertiary experiences and classroom realities - Green, Corrine; Eady, Michelle; Andersen, Peter (Teaching and Learning Inquiry, 2018)
There are many factors that impact student learning, with quality educators being one of the most important elements for student success. Accordingly, the promotion of quality teacher preparation programs has become a priority for tertiary institutions, researchers, policymakers and practitioners. There is a known disparity between tertiary experiences and the classroom reality that leaves graduate teachers feeling unprepared for the teaching profession. Employing a contextualized learning approach such as situated learning theory in teacher preparation programs can reduce this gap and successfully prepare graduate teachers for the teaching arena. This research project surveyed one cohort (n=154) at the conclusion of a four-year initial teacher education program, and again six months after graduation, as well as analyzed the subject outlines of the core final year subjects. The study found that the final year of the program incorporated the key tenets of situated learning theory, integrated theory and practice, and prepared the graduates for the realities of the teaching profession by effectively contextualizing their tertiary learning.